Prevention of The Spread of The Covid-19 Virus - Maya Aprilia (Muhammadiyah International Public Health and Medicine Proceeding, 2021)
Clean and Healthy Lifestyle's Impact in Concern to Covid-19 Prevention. From the beginning of 2020 until now, the COVID-19 pandemic has not yet ended in many countries. COVID-19 has been the reason for more than 991,000 deaths in the world and 8,000 deaths in Indonesia alone. This contagious virus is spreading among humans through droplets, which make it dangerous for a human to make direct contact to one another. Based on government recommendation, Perilaku Hidup Bersih dan Sehat (PHBS) or Clean and Healthy Lifestyle is one of many methods to protect ourselves from COVID-19. Regularly washing your hands with clean water dan consuming healthy foods are part of PHBS or Clean and Healthy Lifestyle which hopefully can grow into a habit to each especially in a pandemic situation like this.